Tatar Literary Criticism at the Turn of the 20th–21st Centuries in the Context of Critical Thought in the Kindred Literatures of the Ural-Volga Region - Galieva, Lyaysan Sh. (The New Research of Tuva, 2025)
The article analyzes key features in the development of Tatar literary criticism at the turn of the 20th — 21st centuries in comparison with the critical discourse of Bashkir and Chuvash literatures. The study covers the period from the 1980s to the first decade of the 21st century, when literary processes were shaped by major socio-political transformations: democratization, the lifting of ideological restrictions, the return of previously banned literary heritage, as well as the simultaneous influences of globalization and national revival. The author demonstrates that this transitional stage in all three Turkic literary traditions was marked by a search for new methods and forms of critical analysis, a turn toward national origins, an expansion of thematic and genre diversity, and an increasing inclination toward polemics and the essayistic mode. Special attention is paid to differences in the development of criticism: while Tatar and Bashkir traditions exhibited a shared tendency toward reinterpreting the national canon, Chuvash criticism was engaged in internal debates regarding the legacy of socialist realism and efforts to evaluate its accomplishments through comparative assessments with neighboring literatures. The article emphasizes that, despite certain crisis phenomena, Tatar literary criticism at the turn of the century preserved its potential for renewal. This was made possible by the engagement of new participants — writers, philologists, and readers — as well as by institutional changes related to the advancement of national education and the humanities. This study draws on materials published in leading literary journals along with recent research on the history and theory of the literary process in the Ural-Volga region.